Transgelins: Cytoskeletal Associated Proteins Implicated in the Metastasis of Colorectal Cancer - Liu, Jingwen; Zhang, Yingru; Li, Qi; Wang, Yan (Frontiers in Cell and Developmental Biology, 2020)
Actin-binding proteins (ABPs) are proteins that could bind to actin or actin fibers.As a family of actin-binding proteins , the transgelins can change the structure and morphology of the cytoskeleton by binding actin directly.The transgelin family comprises transgelin-1,transgelin-2 and transgelin-3 three isoforms,they are both directly and indirectly involved in many cancer-related processes such as migration, proliferation, differentiation or apoptosis.Generally, the expression and biological role of the transgelins seem to differ among various types of tumor cells and stroma, and possibly change during tumor progression.Especially in colorectal cancer(CRC), transgelin-1 is firstly as a tumor suppressor to down-regulate its expression,suggesting an early event in CRC development,then increasing its expression when advanced disease. The expression of transgelin-2 increases with the CRC progression. Transgelin-3 is only expressed in neurons and is not associated with CRC.Moreover,previous studies demonstrated that a positive correlation between transgelin-1 and transgelin-2 level and lymph node metastasis,and down-regulate their expression can inhibit metastasis of CRC.These evidences suggest that transgelin-1 and transgelin-2 may be as new potential biomarkers and therapeutic targets in CRC patients.